2016
DOI: 10.3747/co.23.2989
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation Costs in Attempted Breast-Conserving Surgery: A Decision Analysis

Abstract: Background Breast-conserving surgery (bcs) is the preferred surgical approach for most patients with early-stage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 45 publications
0
28
0
2
Order By: Relevance
“…The ability to discern healthy tissue from tumor tissue could potentially improve intraoperative margin evaluation during breast-conserving surgery and reduce the number of re-excisions, which are currently reported to be as high as 20% of patients. [1][2][3][4][5][6] Previous research showed the potential of DRS to provide surgical guidance during breast-conserving surgery based on the ability of DRS to discriminate healthy breast tissue from tumor tissue. [7][8][9][10][11] The reported accuracies for discriminating healthy breast tissue from tumor tissue reached up to 92% in vivo, albeit that these results were obtained in patients who did not have any "neoadjuvant chemotherapy."…”
Section: Introductionmentioning
confidence: 99%
“…The ability to discern healthy tissue from tumor tissue could potentially improve intraoperative margin evaluation during breast-conserving surgery and reduce the number of re-excisions, which are currently reported to be as high as 20% of patients. [1][2][3][4][5][6] Previous research showed the potential of DRS to provide surgical guidance during breast-conserving surgery based on the ability of DRS to discriminate healthy breast tissue from tumor tissue. [7][8][9][10][11] The reported accuracies for discriminating healthy breast tissue from tumor tissue reached up to 92% in vivo, albeit that these results were obtained in patients who did not have any "neoadjuvant chemotherapy."…”
Section: Introductionmentioning
confidence: 99%
“… 13 The financial costs of reoperation are also considerable. 14 Population-based studies in the USA 10 and England 11 estimate the rate of reoperation ranges between 20% and 30%, though recent data suggest a downtrend in rates following the dissemination of clinical guidelines regarding surgical margins. 15 Previous Australian data are limited; a rate of 30% was estimated based on linked registry from Western Australia, 1998–2000.…”
Section: Introductionmentioning
confidence: 99%
“…All studies used a cost–benefit analysis and focused on the perioperative phase. Two studies used a prediction model, whereby a decision‐tree analysis was undertaken to model the cost impact of re‐excision following BCS. Only direct medical costs were reported; indirect costs (not directly accountable to the operation) and intangible costs (unquantifiable cost relating to an identifiable source) were not estimated in any of the reviewed literature.…”
Section: Resultsmentioning
confidence: 99%
“…Although there have been a number of reports describing the cost burden associated with reoperations after breast surgery, there has been no attempt to review or synthesize this literature. Moreover, investigators have attempted to define the costs of reoperations after BCS using best estimates of patient charges or decision models that use hypothetical cohorts. Although there is an obvious cost burden to health systems, the idiosyncratic nature of costing methodologies used creates uncertainty around the magnitude and location of cost drivers across the BCS care pathway.…”
Section: Introductionmentioning
confidence: 99%